CHEMICAL COMPOSITION OF AMBER-BASED MACERATE: METHODS OF ANALYSIS AND RESULTS - Voronina-Tuzovskykh, Юлія; Mikulenko , Олександр; Bondar, Олена; Kurmakova, Ірина; Pleshakov , Олексій (Biota. Human. Technology, 2024)
Purpose of the work. To investigate the chemical composition of the amber-based complex-macerate (TM IL SAV AMBER) by qualitative and quantitative analysis. To carry out elemental analysis of organic and inorganic components, as well as the content of succinic acid and vitamins in order to identify the potential as a raw material for cosmetic and pharmaceutical production. Methodology. The content of carbon, hydrogen, nitrogen, sulphur and oxygen in the organic part of the macerate complex was determined by conventional methods of quantitative analysis. The mass fraction of ash was determined by the mass loss during combustion of organic components in the air atmosphere at a temperature of 550°C. The elemental composition of the inorganic part was determined by the X-ray fluorescence method using an EXPERT 3L analyzer; vitamins and succinic acid were determined using a liquid chromatograph Hewlett-Packard HP 1100. The acid number and peroxide number of the complex-macerate was determined by the titrimetric method (titrant sodium hydroxide solution and thiosulfate solution, respectively); iodine number - by refractometry; mass fraction of moisture - by drying to constant weight (arbitration method). The obtained general indicators were compared with the corresponding indicators of fatty edible oils. Scientific novelty. The composition (elemental and composition) of the amber-based complex-macerate is determined and the prospects of its use as a raw material for the production of new pharmaceutical and cosmetic preparations are presented. Conclusions. The results of qualitative and quantitative analysis of the determination of the basic composition of the amber-based macerate complex are consistent with the literature data on the composition of amber; the presence of such vitamins as A, E, K, F, PP, D and vitamins of B complex group and elemental composition indicate the prospects of using the complex in the cosmetic and pharmaceutical industries.